2021
DOI: 10.3390/molecules26061619
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Red Yeast Rice, a Traditional Fermented Food in Japan and East Asia: Its Characteristic Ingredients and Application in the Maintenance and Improvement of Health in Lipid Metabolism and the Circulatory System

Abstract: Red yeast rice has been used to produce alcoholic beverages and various fermented foods in China and Korea since ancient times; it has also been used to produce tofuyo (Okinawan-style fermented tofu) in Japan since the 18th century. Recently, monacolin K (lovastatin) which has cholesterol-lowering effects, was found in some strains of Monascus fungi. Since statins have been used world-wide as a cholesterol-lowering agent, processed foods containing natural statins are drawing attention as materials for primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 73 publications
(99 reference statements)
0
13
0
Order By: Relevance
“…Fermented red yeast rice (RYR), obtained from the fermentation of rice (Oryza sativa) by the yeast Munascus purpureus, is an ancient supplement from the East. It is rich in bioactive compounds (monacolines) with a lowering effect on plasma lipids and LDL-C [193,194].…”
Section: Red Yeast Rice (Ryr)mentioning
confidence: 99%
“…Fermented red yeast rice (RYR), obtained from the fermentation of rice (Oryza sativa) by the yeast Munascus purpureus, is an ancient supplement from the East. It is rich in bioactive compounds (monacolines) with a lowering effect on plasma lipids and LDL-C [193,194].…”
Section: Red Yeast Rice (Ryr)mentioning
confidence: 99%
“…There were no statistically significant differences by gender and approximately two-thirds of the subjects were women in the group CYP3A4 and MON-K, while in the NO-CYP3A4 users were close to one-third. Menopausal state was present in 71.4% of CYP3A4 women, 85.7% of the NO-CYP3A4 and 45.4% of MON-K. Other drugs % Other lipid lowering 9.5 (1) 21.0 (1) 0 0.130 Hormones 4.8 (2) 10.5 (2) 18.7 (3) 0.351 BP lowering 57.1 (4) 36.8 (5) 18.7 (6) 0.076 Anti-platelets/anti-coagulant 23.8 (7) 26.3 (8) 0 0.099 Glucose lowering 23.8 (9) 15.9 (10) 0 0.134 Anti-inflammatory/analgesic % Oral drugs 42.8 (11) 42.1 (11) 18.8 (11) 0.245 Topical 33.3 (12) 36.8 (12) 31.2 (12) 0.939 Nutraceuticals % 0 5.2 (13) 87.5 (14) <0.001 CYP3A4: volunteers in treatment with lovastatin, atorvastatin or simvastatin; NO-CYP3A4: volunteers in treatment with rosuvastatin or pravastatin; MON-K: volunteers in treatment with monacolin K (red yeast rice, RYR); SBP: systolic blood pressure; DBP: diastolic blood pressure; HR: heart rate; Delta-CHOL: Cholesterol variation after treatment. (1) ezetemibe; (2) levothyroxine; (3) levothyroxine, norethisterone acetate; (4) amlodipine, atenolol, bisoprolol, candesartan, irbesartan, mesartan, metoprolol tartrate, nebivolol, rampiril, perindopril, valsartan, zofenopril calcium salt; (5) atenolol, bisoprolol, doxazosin, enalapril, rampiril, valsartan; (6) rampiril, olmesartan; (7) apixaban, clopidogrel, digitalis glycoside; (8) clopidogrel, acetylsalicylic acid; (9) dulaglutide, insulin, metformin; (10) metformin; (11) tapentadol, cortisone; (12) cortisone; (13) berberine, polyunsaturated ω-3 fatty acids; (14) policosanols, berberine...…”
Section: Resultsmentioning
confidence: 99%
“…Besides, Med-D in combination with red yeast rice (RYR) reduced low-density lipoproteins (LDL) in individuals with statin intolerance [4]. RYR, obtained by the traditional fermentation of cooked rice kernels with a Monascaceae mold, Monascus purpureus [5], by solid-state culture method [6] or by liquid-state culture method [6], contains monacolin K, a weak reversible inhibitor of 3-hydroxy-3-methylglutaryl-coenzyme A reductase, the rate-limiting enzyme of the mevalonate pathway of cholesterol synthesis [7]. Although citrinin (CIT), a nephrotoxic and hepatotoxic mycotoxin, is produced by Monascus spp., it has been reported that dietary supplements contained CIT below the established limit of detection [8].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, extensive research has been undertaken to identify ingredients and components that display some clear physiological activity, namely improving intestinal transit [ 1 , 2 ] and the immunological system [ 3 ], or reducing cholesterol [ 4 ], blood glucose [ 5 ], arterial hypertension [ 6 ], and obesity [ 7 ].…”
Section: Introductionmentioning
confidence: 99%